Pengaruh E-Promotion Dan User Interface Terhadap Keputusan Pembelian Di Tokopedia (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Ferdian Dwi Putra; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to examine the effect of e-promotion and user interface on purchasing decisions in shopping applications at tokopedia for student of the Faculty of Economics and Business Universitas Islam Malang. The sample used in this study was 96 students majoring in management class 2017. Samples were taken based on nonprobability sampling technique and used purposive sampling. The method in data collection used in this study is a questionnaire. The independent variable consists of e-promotion and user interface while the dependent variable in this study is the purchase decision which is measured using multiple linear regression analysis. The results showed that simultaneously the independent variables had a significant effect on the dependent variable. Based on the partial test results, the variables of e-promotion and user interface have a significant effect on purchasing decisions for students of the Faculty of Economics and Business, Islamic University of Malang. Keywords: E-promotion, User Interface and purchase decision.